Lysophosphatidic acid suppresses apoptosis of high-grade serous ovarian cancer cells by inducing autophagy activity and promotes cell-cycle progression via EGFR-PI3K/Aurora-AThr288-geminin dual signaling pathways - Zhao, Haile; Jia, Peijun; Nanding, Kathleen; Wu, Man; Bai, Xiaozhou; Morigen, Morigen; Fan, Lifei (Frontiers in Pharmacology, 2022)
Lysophosphatidic acid (LPA) and Geminin are overexpressed in ovarian cancer, and increasing evidence supports their contribution to ovarian tumor development. Here, we reveal that geminin depletion induces autophagy suppression, enhances reactive oxygen species (ROS) production and apoptosis of high-grade serous ovarian cancer (HGSOC) cells. Bioinformatics analysis and pharmacological inhibition studies confirm that LPA activates geminin expression in the early S phase in HGSOC cells via LPAR1/3/MMPs/EGFR/PI3K/mTOR pathway. Furthermore, LPA phosphorylates Aurora-A kinase on Thr288 through EGFR transactivation, and this event potentiates additional geminin stabilization. In turn, overexpressed and stabilized geminin regulates DNA replication, cell-cycle progression, and cell proliferation of HGSOC cells. Our data provide potential targets for enhancing the clinical benefit of HGSOC precision medicine.